Буденна свідомість та практики в площині повсякденності релігії - Борейко, Юрій; Boreyko, Yuriі (Східноєвропейський національний університет імені Лесі Українки, 2014)
Статтю присвячено дослідженню релігійних знань та цінностей як компонентів буденної релігійної сві-домості, з’ясуванню значення релігійних практик у конструюванні повсякденності релігії. Здійснений аналіз доводить необхідність вивчення буденної свідомості та практики як джерел повсякденності релігії в їх не-розривному зв’язку. The article is dedicated to discovering knowledge and values as components of everyday religious consciousness. It was ascertained the meaning of religious practices in constructing of everyday religion. Performed analyses proves the necessity of studying of consciousness and practice as sources of religion commonness in their inseparable connection. Religious commonness influences not only world outlook of an individual, but also his activity and results of this activity, forms specific model of behavior. Symbolic universe that connects consciousness with objective external world is knowledge that in religious sphere has its own specific character, creates quite isolated significative sub–universe and its range stretches from special knowledge of theological basics till everyday understanding of standards of behavior. Everyday knowledge is expressed in the system of beliefs that appears as religious knowledge on divine reality, world, itself and is considered to be understandable as such. In comparison with scientific knowledge, peculiarities of everyday knowledge are its unconscious usage, absence of prior system of showing and verbal character. Values raised by everyday life are its grounding and have a range of essential peculiarities. In the process of everyday settling of reality human perceives and accepts specific axiological set. Essential index in defining of meaningful values of any society is religion. Everyday consciousness by slowly changing in the process of sociocultural transformations still saves invariable its valuable core. The notion of religious practices gives opportunity to examine practical dimension of religious knowledge and values. In everyday consciousness through religious practices there takes place a reduction of conceptual constructs of religion that is predicted by hidden subjective motivations and intentions of existential plan. Religious practices regulate everyday life of the believers in different spheres. In the process of interaction of a subject with a personified subject of spiritual world in the context of commonness religious experience is formed and it lets us define valuable grounding of religious behavior and religious socialization of a personality.
Everyday Consciousness and Practices in the Sphere of Religion Commonness
Keywords: повсякденність релігії; буденна релігійна свідомість; буденне знання; цінності; релігійні практики; religion commonness; everyday religious consciousness; knowledge; values; religious practice